Efficacy and Safety of Rosuvastatin versus Atorvastatin in the Treatment of Ischemic Stroke: A Systematic Review and Meta-Analysis Based on Randomized Controlled Trials - Cui, Kaiwen (Exploring Science Academic Conference Series, 2026)
This study aimed to compare the efficacy and safety of rosuvastatin and atorvastatin in the treatment of ischemic stroke. Literature published before January 1, 2026 was retrieved from five databases, including PubMed, Web of Science, CNKI, Wanfang , and VIP. Eligible studies were screened according to the predefined inclusion and exclusion criteria. The included studies were comprehensively analyzed based on the primary outcome measures of blood lipid parameters, including low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL -C), and total cholesterol (TC), as well as the secondary outcome measures of carotid atherosclerosis, including intima -media thickness (IMT) and plaque area, together with the neurological deficit score assessed by the National Institutes of Health Stroke Scale (NIHSS). A total of 12 randomized controlled trials were included in the final analysis. The results showed that, compared with atorvastatin, rosuvastatin demonstrated superior effects in r educing blood lipid levels and improving carotid IMT and NIHSS scores. Overall, rosuvastatin exhibited better clinical efficacy in the treatment of ischemic stroke. Although both agents showed broadly comparable effects in lipid lowering, stabilization of carotid atherosclerotic plaques, and improvement of neurological function, rosuvastatin appeared to have a more favorable safety profile than atorvastatin. Nevertheless, further multicenter, large -scale, high -quality randomized controlled trials are still required to confirm its efficacy and safety.